The bookseller bird - Law, Felicia; Evans, Nicola (Minneapolis, MN : Picture Window Books, 2006)
A visiting bird tries to talk Bamboo, Velvet, and Beak into buying his set of books.
Keywords: Rain forests; Pandas; Zebras; Birds